Immobile lipopolysaccharides and outer membrane proteins differentially segregate in growing Escherichia coli - Sandip Kumar; Patrick G. Inns; Scott Ward; Valentine Lagage; Jingyu Wang; Renata Kaminska; Martin J. Booth; Stephan Uphoff; Edward A. K. Cohen; Gideon Mamou; Colin Kleanthous (Proceedings of the National Academy of Sciences, 2025)
The outer membrane (OM) of gram-negative bacteria is a robust, impermeable barrier that excludes many classes of antibiotics. Contrary to the classical model of an asymmetric lipid bilayer, recent evidence suggests the OM is predominantly an asymmetric proteolipid membrane (APLM). Outer leaflet lipopolysaccharides (LPS) that surround integral β-barrel outer membrane proteins (OMPs) are shared with other OMPs to form a supramolecular network in which the levels of OMPs approach those of LPS. Some of the most abundant OMPs in the Escherichia coli OM are trimeric porins. How porins and LPS are incorporated into the OM of growing bacteria is poorly understood. Here, we use live-cell imaging and microfluidics to investigate how LPS, labeled using click chemistry, and the porin OmpF, labeled using the bacteriocin colicin N, are incorporated into the E. coli OM. Diffraction-limited fluorescence microscopy shows OmpF and LPS to be uniformly distributed and immobile. However, clustering of both macromolecules becomes evident by superresolution microscopy, which is also the case for their biogenesis proteins, BamA and LptD, respectively. Notwithstanding these common organizational features, OmpF insertion into the OM is cell-cycle-dependent leading to binary partitioning and strong polar accumulation of old OmpF. Old LPS on the other hand is diluted ~50% at each division cycle by new LPS, resulting in only mild polar accumulation of preexisting LPS. We conclude that although LPS and OMPs are destined to form the APLM their insertion dynamics are fundamentally different, which has major implications for understanding how the OM is assembled.